PROSES KREATIF EDDIE CAHYONO DALAM PENCIPTAAN FILM SITI - Nugroho, Widhi; Adji, Titus Soepono; Wastiwi S, Sri (Seni Media Rekam ISI Surakarta, 2017)
The Siti film directed by Eddie Cahyono deserves to be appreciated as a work of long fiction films by creative production. Evidently, the film funded with a budget under 150 million rupiah, able to deliver it into the nomination of film festivals, even this film is able to win awards in a number of prestigious film festivals in various countries. It can not be separated from the creative work of Eddie Cahyono as a scriptwriter and director at the filmThis creative work isdue to his role as a meticulous person,looking deeply,appreciating the role of women,elevating her dignity and then transferring it in a film. Siti is a reflection of women living in confinement, debt induced,taking care of families and husbands paralyzed by sea accidents as fishermen.Siti just want to be free and independent of it all, it is a statement to be conveyed Eddie Cahyonothrough this film.The stages in reviewing this creativity include Eddie Cahyono's work steps in writing film scenarios that include the process of finding ideas, themes, story settings, story conflicts to the whole siti movie scenario,while to examine the directing process including the preproduction process (script breakdown, casting, reading, rehearsal), production process (shooting in the field) and post-production process through the mise en scene in the Siti film.Keywords: Siti film,creativity,scriptwriter,and director